Given:
The recursive formulae are:
(a)
![f(n)=f(n-1)-2; f(1)=8](https://img.qammunity.org/2022/formulas/mathematics/college/vfgu1fvvsd1877wts30c67nciwtja7fuxs.png)
(b)
![f(n)=5+f(n-1); f(1)=0](https://img.qammunity.org/2022/formulas/mathematics/college/cwlgzbayuxyu6p3gn2i51zi1hykxym7q4j.png)
To find:
The explicit equation.
Solution:
A recursive formula of an arithmetic sequence is
and f(1) is the first term.
Where, d is the common difference.
The explicit formula is
![f(n)=a+(n-1)d](https://img.qammunity.org/2022/formulas/mathematics/college/nyr8leqllsp6w4ox49bvxjn36bgxdtsoce.png)
where, a is first term and d is common difference.
(a)
We have,
![f(n)=f(n-1)-2; f(1)=8](https://img.qammunity.org/2022/formulas/mathematics/college/vfgu1fvvsd1877wts30c67nciwtja7fuxs.png)
Here, first term is 8 and common difference is -2. So, the explicit formula is
![f(n)=8+(n-1)(-2)](https://img.qammunity.org/2022/formulas/mathematics/college/nvacdnaxz226e45al9vv37i3fmyl562s8h.png)
![f(n)=8-2n+2](https://img.qammunity.org/2022/formulas/mathematics/college/esymx0n44yszovlgr2a4xa5784kutu0g8r.png)
![f(n)=10-2n](https://img.qammunity.org/2022/formulas/mathematics/college/2zkij109escch86nzzegr60d9nsqbusew3.png)
Therefore, the explicit formula is
.
(b)
We have,
![f(n)=5+f(n-1); f(1)=0](https://img.qammunity.org/2022/formulas/mathematics/college/cwlgzbayuxyu6p3gn2i51zi1hykxym7q4j.png)
Here, first term is 0 and common difference is 5. So, the explicit formula is
![f(n)=0+(n-1)(5)](https://img.qammunity.org/2022/formulas/mathematics/college/svt4mssimt65e0wkzlcv7k0kdtidjcrwg0.png)
![f(n)=5n-5](https://img.qammunity.org/2022/formulas/mathematics/college/j5riczfim28a7ikyodpxti8ffkjqynwglf.png)
Therefore, the explicit formula is
.